The Relevance of Triangular Theory of Love in Devon Daniels’ Meet You in the Middle - Calista, Salsabila Nova; Pasopati , Rommel Utungga (Journal Corner of Education, Linguistics, and Literature, 2024)
This study investigates the profound love shared between the main characters, Kate Adam and Ben Mackenzie, in the novel "Meet You in the Middle" by Devon Daniels drawing from Robert J. Sternberg’s concept of Triangular Theory of Love. The study aims to understand the realization that is underlying components of love by contributing through the triangular theory of love in their relationship. The researchers employ qualitative approach, focusing on the contexts and subjective interpretations. The analysis uncovers that Kate Adam and Ben Mackenzie attain triangular theory of love by embodying the fundamental components of intimacy, passion, and commitment within their relationship.